Nine new species of Horismenus Walker (Hymenoptera: Eulophidae) in Brazil, with an emphasis on the fauna of one of the largest tropical forests on the planet, the Atlantic Forest - Pikart, Tiago G.; Schoeninger, Karine; Costa, Valmir A.; Hansson, Christer; Zanuncio, José C.; Serrão, José E. (Zootaxa, 2024)
Horismenus Walker (Hymenoptera: Eulophidae) is one of the largest genera in Eulophidae, and additional collecting in tropical America will undoubtedly add numerous new species. Here we describe nine new species of Horismenus from material collected in Brazil, mainly in Atlantic Forest remnants: H. amplicavus sp. nov., H. atlanticus sp. nov., H. bilineatus sp. nov., H. crastoensis sp. nov., H. novaiguassuensis sp. nov., H. parvicavus sp. nov., H. pterathrix sp. nov., H. sagittatus sp. nov., and H. saueri sp. nov. In addition, we also provide images, diagnoses, and comments to facilitate the identification of each new species.